Regulation of Cabinet Relations with the Government of Aceh within the Framework of a Presidential System - Ridwansyah, Muhammad; Isra, Saldi; Nurbaningsih, Enny; Fahmi, Khairul (SCAD Independent, 2025)
Law Number 11 of 2006 concerning the Government of Aceh allows the Governor of Aceh as Head of Government to be equalized with the Minister, but it is constrained by the mechanism for filling the position. From the aspect of the authority stated in Law Number 11 of 2006, it provides considerable authority in the issues of land, oil and gas, and the flag and symbol of Aceh. This idea will examine the relationship between the Aceh Government and the cabinet in depth to clarify the authority of the three above. The issues of land, oil, and gas, the flag and symbol of Aceh are held by three ministries (Ministry of Agrarian Affairs and Spatial Planning BPN, Ministry of Energy and Mineral Resources, and Ministry of Home Affairs) must be adequately resolved and handed over to the Governor of Aceh as Head of the Aceh Government so that the principles of specialness and privileges accommodated by Article 18B of the 1945 Constitution can be realized by the Aceh region which is decentralized. Management of the relationship between the Cabinet and the Aceh Government is an effort to strengthen the presidential system because the presidential system is now burdened by party elites, also impacting the Governor of the asymmetric decentralized region.